Sex, Crime, Drugs, and Just Plain Stupid Behaviors The New Face of Young Adulthood in America - Salvatore, Christopher (Springer International Publishing, 2018)
Sex, Crime, Drugs, and Just Plain Stupid Behaviors: The New Face of Young Adulthood in America is written for students, parents, and practitioners to provide insight into how emerging adulthood impacts the lives and behaviors of young people. Salvatore provides an insightful examination of the evolution of emerging adulthood as a distinct stage of the life course, bridging the gap between macro-level social forces and micro-level life experiences and behavior. Chapters discuss the influence of social institutions such as marriage, the family, religion, and parenting on behavior during emerging adulthood. Exploration and sensation-seeking are examined in relation to the behaviors and identity of emerging adults alongside issues such as criminal offending, substance use, and other risky/dangerous behaviors. Finally, the book concludes with informed policy recommendations for social institutions such as educational establishments and the criminal justice system on how to work with emerging adults. .